Decompression sickness and recreational scuba divers. Issue 4 (1st July 2003) - Nakayama, H; Shibayama, M; Yamami, N; Togawa, S; Takahashi, M; Mano, Y
Abstract : Objectives: The aim of this study is to clear the status of recreational scuba divers in Japan for promoting safety in recreational diving. Methods: A five year (from 1996 to 2001) questionnaire survey was performed of Japanese divers at the Osezaki area in Japan. The subjects of this survey included diving instructors as well as recreational divers. Based on the obtained data, the study investigated the theory predicted incidence of decompression sickness (DCS) among Japanese recreational divers. Results: The average (SD) of the maximum depth for diving was 37.4 (13.1) metres, which was deeper than the recommended depth of recreational diving. The incident rate of nitrogen narcosis (12%) was the most frequent, followed by barotraumas of the ear (11%) and barotraumas of the paranasal sinus (5.6%). The rate of DCS was 1.9 % (60 divers) during investigated period, and that DCS occurred once per 19 011 dives in calculation. Conclusions: This investigation showed that the status of leisure diving in Japan is still serious, because DCS would be expected to occur once a weekend in Japan. It is speculated that many divers may develop DCS while moving through high altitudes after diving, particularly at the Osezaki diving spot in Japan. Based on the results of this study, it is emphasised that every Japanese leisure diver should take an increasing interest in the safety of diving activity.